Perkembangan Fisik Anak Dan Psikososial Remaja - Ulfa Hermaini; Fauziah Nasution; Risqi Aulia Safitri; Qisti Aqila Rahma; Habib Munawir Hasibuan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This paper aims abnalyze The physical and psychosocial development of children and adolescents is a broad topic and complex. Children begin to develop the ability to think, learn, and remember, and begin to develop the ability to control emotions and interact with people other. In adolescence, individuals experience a transition between childhood and adulthood adult life is characterized by biological growth and development and psychological. Children's physical and psychosocial development of adolescents can begin with an explanation of the importance of understanding physical and psychosocial development during childhood and adolescence. Matter This is because this period is a very important period in a person's life, in where many significant changes and developments occurred. Additionally, understanding of Physical and psychosocial development during childhood and adolescence is also very important for parents, teachers and health workers in providing appropriate care and upbringing. Physical development during childhood and adolescence includes growth and development of body organs, nervous system, and motor abilities. Meanwhile development Psychosocial includes emotional, social and cognitive development. During childhood, Physical and psychosocial development is greatly influenced by the environment and upbringing accepted. Meanwhile, during adolescence, physical and psychosocial development is influenced by internal and external factors, such as hormonal changes, social environment, and pressure from friends peer. In discussing children's physical development and adolescent psychosocial development, it needs to be emphasized that each individual has different developments, depending on factors which influences it.